Confidence College – an online education tool for neurology patients - Angus-Leppan, Heather; Caulfield, Alice; Moghim, Melika M; Nightingale, Jennifer; Sloan, Rob; Stables, Tom; Oates, Michael; Porter, Bernadette; Schrag, Anette (Advances in clinical neuroscience & rehabilitation, 2022)
COVID-19 and its aftermath highlight the importance of patient self-care and involvement in monitoring and improving their health. Resources to guide this are essential. Our objective was to create a web-based patient education tool, to facilitate patient education and empowerment for people with epilepsy, multiple sclerosis and Parkinson’s disease, available without cost to patients, carers and clinicians. This project was conducted within community and secondary neurology services. Patients and their carers were involved in designing, reviewing and revising the tool, as equal partners with clinicians and digital engineers. A web-based design template was developed with graphics and links to enable patients to create personalised plans. Participants are patients, carers, clinicians (neurology consultants and specialist nurses), neurological charities, the London Neuroscience Clinical Network, NHS England and Shift.ms (a service design team with experience in creating digital services for individuals living with neurological conditions). Shift.ms conducted in-depth interviews. Clinicians used evidence from personal and PubMed databases. Shift.ms analysed and co-ordinated the responses, and designed the pilot tool. Confidence College provides a delivery model for patient education relating to multiple sclerosis, epilepsy and Parkinson’s disease. It requires follow-up evaluation regarding uptake. This web-based accessible patient empowerment tool has no limit on recurrent use, low maintenance costs and no additional costs in up-scaling the number of users. It is ideally suited for use during and after the COVID-19 pandemic.